Exploratory study of the prevalence of food addiction and its relationship with executive functioning, depression, and reinforcement sensitivity in a sample of Mexican adults - Téllez-Rodríguez, Marybeth Alejandra; Amaya-Hernández, Adriana; Ortega-Luyando, Mayaro; Serrano-Juárez, Carlos Alberto; Yáñez-Téllez, Guillermina; López-Alonso, Verónica Elsa; Mancilla-Diaz, Juan Manuel; Escartín-Pérez, Rodrigo Erick (Frontiers in Public Health, 2023)
Introduction The study of food addiction (FA) has become relevant due to its high prevalence, the negative impact on quality of life, and its association with neuropsychological and psychiatric symptoms. Several studies have provided scientific support for these associations, however, the results are contradictory. Additionally, studies have unsuccessfully elucidated the true nature of the failures in executive functioning in people with FA symptomatology, particularly when it comes to executive deficits. Therefore, the purpose of this research was to establish whether the presence of executive dysfunction, depressive symptoms and binge eating problems, as well as high reward sensitivity entails a greater severity in FA traits and high body mass index (BMI) in a sample of Mexican adults. Methods The sample consisted of Mexican men and women between 21–59 years (n = 36); who completed self-report questionnaires and performance tests to measure the study variables. Additionally, BMI was estimated with self-reported height and weight. Results Our results showed that a high number of FA symptoms were associated with higher executive dysfunction scores, greater reward sensitivity, and more severe depressive and binge eating problems. Furthermore, factors that are more strongly associated with higher scores of FA include severe executive deficits, greater activation of the punishment avoidance system, and persistence in the search for reward when the depressive symptoms increased. The factors that best explained changes in the estimated BMI of women were a decreased crystallized intellectual capacity and the inability to control food intake as the number of FA symptoms increased. Discussion In summary, the cognitive functioning profile characterized by general failure of the executive functioning, as well as a greater activation of the Punishment Avoidance System and persistence in the search for reward, were associated with greater severity of FA symptoms, especially when the depressive symptomatology was severe. In parallel, the psychopathology in participants associated with FA confirms the contribution of anxious and depressive symptomatology and borderline personality traits which could facilitate the expression of clinically relevant FA symptoms in women. Finally, we found that decreased crystallized intellectual capacity and inability to control food intake were linked to higher BMI when the number of FA symptoms increased.